Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

7+3(s-4t) simplify the expression

Sagot :

7+3(s-4t)=7+(3s)-3*4t)=7+3s-12t
Answer=7+3s-12t
luana
[tex]7+3(s-4t)=\ \ \ \ \ \ \ \ \ |omit\ the\ bracket\\\\\boxed{7+3s-12t}[/tex]